2012
DOI: 10.1515/bmt-2012-4246
|View full text |Cite
|
Sign up to set email alerts
|

Improving the sensitivity of optical biosensors by means of Bloch surface waves

Abstract: One factor limiting the performance of Surface Plasmon Resonance (SPR) biosensors is the width of the resonance that basically originates from metal absorption. In contrast, comparable sensing schemes based upon the concept of Bloch surface waves (BSW) have been proposed. As such sensors are prepared from dielectric materials only, losses as well as the resonance width decrease significantly in comparison to SPR. By preparing BSW stacks that feature a similar resonance position as Gold based SPR sensors, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Surface waves which are confined to the interface between a homogeneous medium and a multilayer dielectric structure (MDS) [ 33 ] such as a finite one-dimensional photonic crystal (1DPhC) or Bragg mirror have found a large number of applications similar to the SPPs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Light confinement in the surface waves, which are referred to as Bloch surface waves (BSWs), occurs near the multilayer surface and it is caused by the total internal reflection (TIR) from the homogeneous layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface waves which are confined to the interface between a homogeneous medium and a multilayer dielectric structure (MDS) [ 33 ] such as a finite one-dimensional photonic crystal (1DPhC) or Bragg mirror have found a large number of applications similar to the SPPs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Light confinement in the surface waves, which are referred to as Bloch surface waves (BSWs), occurs near the multilayer surface and it is caused by the total internal reflection (TIR) from the homogeneous layer.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the dielectric materials of the photonic crystal, sensors based on BSWs are characterized by mechanical and chemical stability, thus enabling operation in aggressive environments. Consequently, BSWs have emerged as an effective alternative to SPPs [ 43 , 58 ] and have been utilized in a number of BSW based sensors [ 37 , 38 , 39 , 40 , 41 , 42 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], especially in biosensing [ 37 , 38 , 39 , 40 , 41 , 42 ]. Similarly to SPR based sensors, Bloch surface wave resonance (BSWR) based sensing is with a special emphasis on the measured quantity such as phase [ 46 , 47 , 48 , 49 ] or intensity [ 50 , 51 , 52 , 53 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 Studies of the specific BSW sensing properties have been proposed and demonstrated, including an experimental determination of BSW sensitivity, 22 a direct comparison of BSW and SPP sensors 23 and the experimentally achieved improvement of sensitivity with BSWs in comparison to SPPs. 24 Sensing applications include chemical and biosensing, [25][26][27] gas sensing 28 and fluorescence emission enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include Bloch-like surface waves as proposed in the study of V. Koju et al [3]. In further studies BSWs have been compared to SPPs and extensively exploited in sensing applications [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%